PERAN PERSEPSI NILAI DALAM MEMEDIASI PENGARUH KREDIBILITAS CELEBRITY ENDORSER TERHADAP NIAT BELI PRODUK KOSMETIK MAYBELLINE DI KOTA DENPASAR - Arsinta, Gusti Ayu Pangastuti; Purnami, Ni Made (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
The rapid growth and increasing competition in the business of cosmetic product and also the more selective consumer, makes cosmetic companies do efforts in providing information about the products and create a positive association to attract potential customers. The purpose of this study is to determine the role of perceived value in mediating the effect of celebrity endorser credibility on purchase intention of Maybelline cosmetics products in Denpasar. The sample size was 70 people, determined with non-probability sampling methods, especially incidental and purposive sampling. The analysis technique used was PLS (Partial Least Square). The results of this study indicate that the celebrity endorser credibility influence positively purchase intention and perceived value. Additionally, perceived value has positive impact on purchase intention. Perceived value emerges as variable which mediate partially the effect of celebrity endorser credibility on purchase intention.
Keywords: celebrity endorser credibility, perceived value, purchase intention